Spatial Histories of Occupation Colonialism, Conquest and Foreign Control in Asia - Baillargeon, David; Taylor, Jeremy E. (Bloomsbury Academic, 2022)
This open access book explores how different spatial geographies emerged, adapted or were transformed in various occupied and colonial settings around Asia, showing how the experiences of those living under occupation shaped and was shaped by new interpretations and typologies of 'space'. With case studies across South, Southeast and East Asia and through a variety of disciplinary perspectives, Spatial Histories of Occupation adopts a trans-Asian comparative approach to show how the experiences of occupation and colonialism shifted under particular spatial typologies, particularly in urban, maritime and rural settings. Revealing the similarities, differences and connections that existed between and across different spaces of foreign occupation and colonialism in modern Asian history, this book shows how a focus on historical geography and 'space' can revise our broader categories and conceptualisations related to occupation; be it under colonial, wartime or Cold War powers. The open access edition of this book is available under a CC BY-NC-ND 4.0 licence on www.bloomsburycollections.com. Open access was funded by The European Research Council.